Direct product of finite anti fuzzy normal sub-rings over non-associative rings - Kausar, N. (International Scientific Research Publications, 2020)
In this paper, we define the concept of direct product of finite anti fuzzy normal sub-rings over non-associative and noncommutative rings LA-rings and investigate the some fundamental properties of direct product of anti fuzzy normal sub-rings. Â© 2020 Global Research Online. All rights reserved.